Psicoterapia y derechos humanos, una respuesta a la violencia política: un caso clínico de terapia focal - Wurst, Carmen (2000)
After analyzing the socio-political context in Perú in the 1980s and 190s, this study describes psychotherapeutic services of victims of political violence and treatment using a psychoanalytically oriented brief psychotherapeutic technique with patients who were tortured. The clinical material includes the initial interview, the therapeutic prescriptions, and evaluation of the process.